AN ANALYSIS OF THE INTRINSIC AND EXTRINSIC ELEMENT OF THE POEM “TUHAN, KITA BEGITU DEKAT” BY ABDUL HADI WM - Wahyu Unggul Widodo; Tiara Nurwanti (Journalistics: Journal of English Teaching and Applied Linguistics, 2024)
Poetry is the author's expression as a means of expression in the form of writing with each stanza full of meaning. Therefore, in understanding a poem, in-depth study is needed. This research aims to describe the intrinsic and extrinsic elements contained in the poem “Tuhan, Kita Begitu Dekat” by Abdul Hadi WM The method used is descriptive qualitative with a structural approach originating from the data or poem. Based on research, shows that the results of data analysis of the poem “Tuhan, Kita Begitu Dekat” by Abdul Hadi WM, have several extrinsic elements consisting of theme, feeling, tone, atmosphere, and message as well as the intrinsic element of the poem including diction, concrete words, images, figures of speech and rhyme